DESAIN EKSPERIMEN TAGUCHI UNTUK MENINGKATKAN KUALITAS PUPUK ORGANIK BERBAHAN BAKU KOTORAN KELINCI - Setyanto, Nasir Widha; Riawati, Lely; Lukodono, Rio Prasetyo (JEMIS (Journal of Engineering & Management in Industrial System), 2014)
Currently one of the organic fertilizer started being used is organic fertilizer from rabbit feces. In Pesanggrahan Batu area, there are about 25 farmers in each farmer has about 50 rabbits and joinning to "Paguyupan Ternak Karya Bagus". The problem is there still no standard composition of optimal organic fertilizer made from rabbit feces, so it is necessary to do a research to evaluate the composition of the organic fertilizer made from rabbit feces to get the high content of nitrogen, phosphorus and Kalium. Some factors used in this research related to the raw material for organic fertilizer are rabbit feces, bran, husk and probiotics factor with 3 levels of each factor, so then we selectÂ  experiment with orthogonal array 34 and 9 variations. The chosen orthogonal array table must have a minimum number of raw which is not less than the total number of degrees of freedom- in this research the total degrees of freedom is 8. Then do experiment in laboratory to check nitrogen (N), phosphorus (P) and kalium (K) content in the soil chemistry laboratory UB faculty of agriculture. Based on data analysis we get the combination of the level of high N content is by using a composition of 3000 g rabbit feces, EM4 10 ml and the amount of chaff 200 gr. The combination of the level that has the effect of generating a high phosphorus content value is the amount of rabbit feces at the level of 3000 g, the amount of EM4 at the level of 20 ml and the amount of chaff at the level of 400 g and level combination that has the effect of generating a high kalium content value is the amount of rabbit feces on level of 3000 g, the amount of rice bran at a level of 200 g, the amount of chaff at the level of 400 grams and the amount of EM4 on the level of 20 ml.